The Business Location Decision for Transport Logistics Service Provider - Yeni Sumantri; Imma Widyawati Agustin (Institut Transportasi dan Logistik Trisakti, 2020)
The aim of this research is to identify industrial, trading and services land use to transport flow. The activities of industrial, trading and services have affected volume traffic. Knowledge about the effect of land use on transportation is needed for LSP in determining its business location. This study used proportional samples size to derive transport flow as result of activities in industrial, trading and services land use. Analysis used in this research was multiple regression analysis to perform transportation flow model. The result show that building area and number of employees significantly influence transportation flow within trading and services land use. For industrial land use, characteristics that more influence transportation flow are building area and number of delivery activities.